2020
DOI: 10.1177/1178223420983843
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Outcomes of Treating Advanced Breast Cancer Patients With Palbociclib: A Multicenter Retrospective Cohort Study in Japan—The KBCOG-14 Study

Abstract: Background: Clinical studies have shown that palbociclib improves progression-free survival in hormone receptor–positive (HR+), human epidermal growth factor receptor 2–negative (HER2−) patients with advanced breast cancer (ABC). However, there are insufficient data on its use in a real-world setting in Japan. The aim of this study was to investigate the effectiveness, predictive factors, and safety of palbociclib among Japanese patients in routine clinical practice. Methods: Between December 1, 2017, and Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
4
10
1
Order By: Relevance
“…We found that 84.76% of patients initiated palbociclib with a 125 mg dose, concordant with other real-world studies [ [21] , [22] , [23] , [24] ]. While the recommended starting dose is 125 mg, a more careful approach is given to more fragile patients and/or with relevant comorbidities.…”
Section: Discussionsupporting
confidence: 91%
“…We found that 84.76% of patients initiated palbociclib with a 125 mg dose, concordant with other real-world studies [ [21] , [22] , [23] , [24] ]. While the recommended starting dose is 125 mg, a more careful approach is given to more fragile patients and/or with relevant comorbidities.…”
Section: Discussionsupporting
confidence: 91%
“…Liver metastasis was already suggested to associate with poor prognosis following CDK4/6 treatment in previous studies (30,31). Our study also suggested that liver metastasis was associated with poor response to palbociclib with letrozole.…”
Section: Discussionsupporting
confidence: 79%
“…In Japan, the real-world efficacy of palbociclib was analyzed in 4 retrospective studies (Table 2 ) [ 55 58 ]. Whereas the sample sizes of Japanese real-world studies were small, the efficacy and safety results seem to be consistent with global real-world data.…”
Section: Treatment With Palbociclib In the Real-world Settingmentioning
confidence: 99%